Arylamino Esters As P‐Glycoprotein Modulators: SAR Studies to Establish Requirements for Potency and Selectivity. Issue 8 (26th May 2015) - Teodori, Elisabetta; Dei, Silvia; Floriddia, Elisa; Perrone, Maria Grazia; Manetti, Dina; Romanelli, Maria Novella; Contino, Marialessandra; Colabufo, Nicola Antonio
Abstract A set of basic aryl‐group‐containing compounds was synthesized with the aim of developing potent and selective P‐glycoprotein (P‐gp) modulators that are able to reverse multidrug resistance (MDR). The natures of the spacer (dicyclohexylamine or dialkylamine) and the aryl moieties were modified to investigate selectivity and the mechanism of P‐gp interaction. The inhibitory activities of the compounds toward P‐gp, multidrug resistance‐associated protein 1 (MRP1), and breast cancer resistance protein (BCRP), the most relevant ATP binding cassette (ABC) transporters for MDR, were evaluated. The mechanism of P‐gp interaction for each compound was investigated with three biological assays: apparent permeability (Papp) determination (B→A/A→B) in Caco‐2 cell monolayers, ATP cell depletion, and inhibition of Calcein‐AM transport in MDCK‐MDR1 cells. These assays allowed us to estimate the selectivity of the compounds for the three efflux pumps and to identify the structural requirements that define the P‐gp‐interaction profile. All dicyclohexylamine derivatives were found to be P‐gp substrates, whereas one dialkylamine derivative was shown to be a P‐gp inhibitor. The good MRP1 activity of one cis/cis isomer highlighted this as a lead candidate for the development of MRP1 ligands.